Retracted : Pemasaran Syariah di Lembaga Keuangan Mikro Islam: Konsep Dan Implementasi Di Puskopsyah DIY - Hendri Hermawan Adinugraha (Perisai : Islamic Banking and Finance Journal, 2017)
Following a rigorous, carrefully concered review of the article published in Perisai Islamic Banking and Finance Journal to article entitled “Pemasaran Syariah di Lembaga Keuangan Mikro Islam: Konsep dan Implementasi di Puskopsyah D.I. Yogyakarta” Vol.1, No.3, pp. 180-199, October 2017, DOI Link: http://doi.org/10.21070/perisai.v1i3.969 This paper has been found to be in violation of the Perisai Islamic Banking and Finance Journal and has been retracted. The article contained redudant material, the editor investigated and found that the paper published in An-Nisbah Jurnal Ekonomi Syariah, Vol.4 No.1, DOI Link:1http://dx.doi.org/0.21274/an.2017.4.1.25-50. The document and its content has been removed from Perisai Islamic Banking and Finance Journal, and reasonable effort should be made to remove all references to the article.